Boosting renewable energy consumption through green innovation and financial development: A sustainability framework for the MENA region - Magdalena Radulescu; Salaheddine Sari-Hassoun; Salim Bourchid Abdelkader; Kamel Si Mohammed; Nicoleta Dascalu (Energy Exploration & Exploitation)
This study examines the dynamic relationships between renewable energy consumption (REC), GDP or economic growth (EG), financial development (FD), and green innovation (GI) in eight MENA countries during the period of 1996–2021 through the lens of lobbying effect, sustainability, and energy transition theories. Employing FMOLS, DOLS, and CCR estimators for long-run coefficients, complemented by Dumitrescu-Hurlin causality tests, we find that there is a statistically significant link between RE and EG at the 1% level; a 1% increase in lnEG corresponds to an increase in lnREC by 1.150%, 0.959%, and 0.553%, respectively. Then, we establish a positive and significant sign at the 1% level between REC and the FD; an upsurge by 1% in lnFD will raise the level of lnREC by 0.113%, 0.050%, and 0.171%, respectively. However, the FMOLS and CCR estimation shows a negative and significant sign at 1% between REC and GI; an increase of 1% in lnGI will decrease the level of lnREC by 0.175% and 0.359%, respectively. We identify one bidirectional causality between REC and FD and two one-way causality, one running from EG to REC and the other from REC to GI. These results suggest the need for policy refinements, particularly in aligning innovation strategies with renewable energy deployment to enhance sustainability in the MENA region.